Ultrathin 2D VOPO4 nanosheets: a novel reinforcing agent in polymeric composites. Issue 102 (21st October 2016) - Zhou, Keqing; Gui, Zhou; Hu, Yuan
Abstract : In the present work, ultrathin VOPO4 nanosheets were prepared through simple ultrasonication in 2-propanol, starting from bulk VOPO4 ·2H2 O chunks. Abstract : In the present work, ultrathin VOPO4 nanosheets were prepared through simple ultrasonication in 2-propanol, starting from bulk VOPO4 ·2H2 O chunks. Subsequently, the ultrathin VOPO4 nanosheets were incorporated into poly(vinyl alcohol) (PVA) matrix as reinforcing agents based on a solution casting method. The ultrathin VOPO4 nanosheets were homogeneously dispersed in PVA matrix and no obvious aggregation was observed, leading to remarkable improvements of thermal stability, flame retardancy, and mechanical properties. With the incorporation of 3.0 wt% VOPO4 nanosheets into PVA, the initial decomposition temperature ( T onset )and half weight loss temperature ( T 50% ) increased by 45 °C and 139 °C, respectively. In addition, the presence of ultrathin VOPO4 nanosheets decreases the decomposition rate of PVA and increases the amount of char residues. Furthermore, the peak heat release rate and the tensile strength of PVA films was decreased by 67% and improved by 45%, respectively, compared to that of neat PVA. These remarkably enhanced properties were mainly attributed the well dispersion, physical barrier effect and catalytic carbonization effect of the ultrathin VOPO4 nanosheets.